Depósitos de las gotas de pulverización sobre las malezas en frijol - Rodrigues-Costa, Andreia C. P.; Martins, Dagoberto [UNESP]; Costa, Neumárcio V.; Pereira, Maria R. R. [UNESP] (Pontificia Universidad Catolica de Chile, 2011)
Weed control failure in common bean (Phaseolus vulgaris L.) production may be related to inappropriate herbicide application techniques. The purpose of this study, therefore, was to evaluate the amount of spray solution deposition that occurred on the weeds, Bidens pilosa L. and Brachiaria plantaginea (Link) Hitch., both within and between rows of common beans. The research was arranged in a randomized block design with four replications. The following 6 spray nozzles were used: flat fan nozzles XR 110015 VS (150 L ha-1) and XR 11002 VS (200 L ha-1); cone nozzles TX VK 6 (150 L ha-1) and TX VK 8 (200 L ha-1); and twin flat fan nozzles TJ60 11002 VS (150 L ha-1) and TJ60 11002 VS (200 L ha-1). The results showed that the loss of the spray solution on the soil occurred mainly within the bean rows and with a high intensity when using a nozzle spraying 200 L ha-1. At 30 days after sowing, the TX (150 L ha-1) nozzle was the only nozzle that promoted deposits of less than 210.0 μL g-1 of dry mass. The spray nozzles showed a good performance in the deposition of the spray solution on the weeds that occurred both within and between the rows. However, for both species there was great variation in individual deposits depending on their location in relationship to the plants.
Spray deposition on weeds of common bean crops
Keywords: Application technology; Bidens pilosa; Brachiaria plantaginea; Nozzle; Phaseolus vulgaris